2017
DOI: 10.3945/ajcn.117.154104
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the causal role of adiposity on disordered eating in childhood, adolescence, and adulthood: a Mendelian randomization analysis

Abstract: Background: Observational studies have shown that higher body mass index (BMI) is associated with increased risk of developing disordered eating patterns. However, the causal direction of this relation remains ambiguous.Objective: We used Mendelian randomization (MR) to infer the direction of causality between BMI and disordered eating in childhood, adolescence, and adulthood.Design: MR analyses were conducted with a genetic score as an instrumental variable for BMI to assess the causal effect of BMI at age 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 52 publications
10
39
0
1
Order By: Relevance
“…Pediatric obesity is a public health concern that affects 17% of children and adolescents in the United States and can have adverse consequences for physical and psychosocial development (Ogden et al, ). There is evidence linking childhood obesity with adult obesity (Herpertz‐Dahlmann et al, ) and disordered eating behaviors such as binge eating (Reed, Micali, Bulik, Davey Smith, & Wade, ), which makes childhood obesity costly to public health. Parents are key stakeholders in and greatly influence their children's health by controlling the foods that are available to them, setting daily schedules, and providing access to healthcare (Arroyo & Segrin, ; Cooley, Toray, Wang, & Valdez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric obesity is a public health concern that affects 17% of children and adolescents in the United States and can have adverse consequences for physical and psychosocial development (Ogden et al, ). There is evidence linking childhood obesity with adult obesity (Herpertz‐Dahlmann et al, ) and disordered eating behaviors such as binge eating (Reed, Micali, Bulik, Davey Smith, & Wade, ), which makes childhood obesity costly to public health. Parents are key stakeholders in and greatly influence their children's health by controlling the foods that are available to them, setting daily schedules, and providing access to healthcare (Arroyo & Segrin, ; Cooley, Toray, Wang, & Valdez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Following the standard approach used by recent Mendelian randomization studies (20,21), the GRS of each metabolite was calculated from SNP genotype data for each study subject. GRS jm denoted the GRS value of the jth metabolite for the mth subject, defined as GRS jm ÂŒ Ă„ l iÂŒ1 b i SNP im .…”
Section: Discussionmentioning
confidence: 99%
“…Mendelian randomization results in a powerful control for confounding factors (e.g., lifestyle and socioeconomic factors) compared with conventional epidemiologic studies (19). Recently, a Mendelian randomization analysis was widely used to investigate the effect of physiological variables on diseases risks (20,21).…”
mentioning
confidence: 99%
“…The three remaining studies did identify some relationship between premorbid BMI and eating disorder pathology or diagnosis. Another prospective study identified a relationship between childhood BMI at age seven and increased eating pathology at age 13 but no relationship between adolescent BMI and eating pathology in adulthood (Reed, Micali, Bulik, Davey Smith, & Wade, 2017). Another prospective study identified a relationship between childhood BMI at age seven and increased eating pathology at age 13 but no relationship between adolescent BMI and eating pathology in adulthood (Reed, Micali, Bulik, Davey Smith, & Wade, 2017).…”
Section: Prospective Risk Factor (Prf) Studies Of Population-based mentioning
confidence: 99%